READING COMPREHENSION FOR SENIOR-GRADE STUDENTS: A FOCUS ON THEMATIC LEARNING - Satriani, Satriani; Rahman, Wiwiek Zulfiana; Ahmad, Gufran; Firmah, Andi (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this study is to determine whether or not the Thematic Learning Approach can significantly improve students' reading comprehension. In this study, a pre-experimental design with one group pretest-posttest was used. This study's population was the third year of MA. Nurul As'adiyah Callaccu, for the academic year 2019/2020, which comprises three classes, The study's overall sample size was 21 students. It was collected using the purposive sampling technique. The reading test and observation checklist were employed as study instruments. The adoption of the Thematic Learning Approach had a substantial influence on students' reading comprehension, according to the findings of this study. It was demonstrated by a t-test value of less than 0.05. The value was (0.00) < (0.05) with a degree of freedom (df) of 20. Based on the study's findings and discussion, the researcher concluded that there was an improvement in the use of theme learning approaches in teaching reading comprehension in the third year of the MA. Nurul As'adiyah Callaccu.